Water-resistant moisture-absorbing and desorbing sheet, method for producing the water-resistant moisture-absorbing and desorbing sheet, and moisture absorbing and desorbing or latent heat exchange element made of the water-resistant moisture-absorbing and desorbing sheet

JP7644410B2Active Publication Date: 2025-03-12JAPAN EXLAN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021065907
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-08
Publication Date
2025-03-12
Estimated Expiration
2041-04-08

AI Technical Summary

Benefits of technology

【0009】 本発明の耐水性吸放湿シートは、耐水性が高く水に浸漬させた後にも低い通気度を有しており、なおかつ十分な透湿性を有する。かかる性能を有する本発明の耐水性吸放湿シートは、例えば結露が発生しやすく、空調システムサイズが厳しく限定されるために高透湿性が要求される車載用換気空調システムの潜熱交換用素子に利用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644410000002
    Figure 0007644410000002
  • Figure 0007644410000001
    Figure 0007644410000001
Patent Text Reader

Abstract

To provide a water-resistant humidity absorbing / releasing sheet which can maintain low gas permeation even when contacting dew condensation.SOLUTION: A water-resistant humidity absorbing / releasing sheet is formed by compounding a sheet-like molding containing humidity absorbing resin particles having a carboxyl group and a binder component with a network polymer containing a cationic polymer and a crosslinking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-resistant moisture absorbing and desorbing sheet, a method for producing the water-resistant moisture absorbing and desorbing sheet, and a moisture absorbing and desorbing or latent heat exchange element comprising the water-resistant moisture absorbing and desorbing sheet as a constituent material. [Background technology]

[0002] Recently, one of the uses of desiccant air conditioning systems is as a dehumidification system without ventilation inside a vehicle. When ventilation is performed inside a vehicle during cold seasons such as winter, the humidity drops and the temperature inside the vehicle drops, so energy must be used to raise the temperature inside the vehicle again. On the other hand, this dehumidification system is advantageous in terms of energy because it can perform dehumidification while maintaining a constant temperature. This type of desiccant air conditioning system requires moisture-permeable paper that is moisture-permeable but also has excellent sealing properties, and conventional techniques suitable for this purpose are described in Patent Documents 1 and 2.

[0003] In these desiccant air conditioning systems, lithium chloride is used as the sorbent in Patent Document 1, and a polymer sorbent is used as the sorbent in Patent Document 2. In particular, organic polymer sorbents are superior to lithium chloride in both moisture absorption and desorption speed and amount, and are therefore more preferably used than lithium chloride.

[0004] However, organic polymer-based sorbents have the property of swelling by absorbing water, and when moisture such as condensation adheres to a moisture-permeable paper in which the sorbent is coated on a base paper, the sorbent components gradually peel off, resulting in a moisture-permeable paper that lacks the airtightness required for the dehumidification system. In response to this problem, Patent Document 3 successfully prevents cracking and peeling during moisture absorption by adding a cationic polymer such as urethane to a coating liquid containing the sorbent, but does not take measures to anticipate adhesion of condensation water, etc., and is insufficient in terms of water resistance. In addition, the water resistance referred to here refers to a performance that does not significantly impair the inherent low air permeability and high moisture permeability when water adheres to the moisture absorption and release sheet due to condensation or rain intrusion. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 180834 [Patent Document 2] International Publication No. 2015 / 111610 [Patent Document 3] JP 2014-180637 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention was devised in consideration of the current state of the prior art, and its object is to provide a water-resistant moisture-absorbing and desorbing sheet that does not lose its inherent low air permeability and high moisture permeability significantly due to condensation, rain intrusion, etc., a method for producing the same, and an element for moisture absorption and desorption or latent heat exchange that uses the water-resistant moisture-absorbing and desorbing sheet as a constituent material. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that by applying a coating liquid composed of a cationic polymer and a crosslinking agent to a moisture absorption and desorption sheet prepared from a coating liquid containing moisture-absorbing resin particles, it is possible to form strong ionic bonds between the polymers, and further covalent bonds through the crosslinking agent, thereby achieving water resistance and at the same time producing a water-resistant moisture absorption and desorption sheet that does not lose its original high moisture permeability, thereby arriving at the present invention.

[0008] That is, the present invention is achieved by the following means. (1) A water-resistant moisture-absorbing and desorbing sheet in which a network polymer containing a cationic polymer and a crosslinking agent is combined with a sheet-shaped molded product containing moisture-absorbing resin particles having carboxyl groups and a binder component. (2) The water-resistant moisture-absorbing and desorbing sheet according to (1), wherein the sheet-like molded product includes a substrate. (3) Moisture permeability of 3000g / m2 ·days or more, and the air permeability after immersion in water at 20°C for 5 minutes and then drying at 120°C for 30 minutes is 5ml / (m 2 The water-resistant moisture-absorbent sheet according to (2), characterized in that the water-resistant moisture-absorbent sheet has a viscosity of not more than 1.0 Pa·s. (4) The water-resistant moisture-absorbing and desorbing sheet according to any one of (1) to (3), wherein the moisture-absorbing resin particles having a carboxyl group have a carboxyl group content of 3 to 10 mmol / g. (5) The content of the moisture-absorbing resin particles having a carboxyl group, the cationic polymer, and the crosslinking agent is 40 to 70 g / m 2 , 4~40g / m 2 and 0.3 to 3 g / m 2 The water-resistant moisture-absorbing and desorbing sheet according to any one of (1) to (4), wherein: (6) The water-resistant moisture-absorbing and desorbing sheet according to any one of (1) to (5), wherein the cationic polymer is a multifunctional polyamine having a primary or secondary amine. (7) The water-resistant moisture-absorbing and desorbing sheet according to any one of (1) to (6), wherein the crosslinking agent has two or more epoxy groups. (8) A method for producing a water-resistant moisture-absorbent sheet, comprising the steps of impregnating a sheet-shaped molded product containing moisture-absorbent resin particles having carboxyl groups and a binder component with a coating liquid containing a cationic polymer and a crosslinking agent, and drying and reacting the same. (9) A moisture absorbing and releasing element or latent heat exchange element comprising the water-resistant moisture absorbing and releasing sheet according to any one of (1) to (7) as a constituent material. (10) A ventilation and air-conditioning system using the element according to (9). Effect of the Invention

[0009] The water-resistant moisture-absorbing and desorbing sheet of the present invention has high water resistance, low air permeability even after immersion in water, and sufficient moisture permeability. The water-resistant moisture-absorbing and desorbing sheet of the present invention having such properties can be used, for example, as a latent heat exchange element in an in-vehicle ventilation and air conditioning system, which is prone to condensation and requires high moisture permeability because the size of the air conditioning system is strictly limited. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing an example of a latent heat exchange element of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. The moisture-absorbing resin particles used in the present invention contain a carboxyl group in the molecule. Such a carboxyl group has the property of adsorbing moisture in the air. The carboxyl group is preferably a salt type, and examples of the cation pair include alkali metals such as Li, Na, K, Rb, and Cs, alkaline earth metals such as Be, Mg, Ca, Sr, and Ba, and organic cations such as NH4 and amines. Among these, cations of alkali metals and alkaline earth metals are preferable from the viewpoint of moisture absorption and desorption speed.

[0012] The amount of carboxyl groups is preferably 3 to 10 mmol / g, more preferably 5 to 8 mmol / g. If the amount of carboxyl groups is less than 3 mmol / g, sufficient moisture absorption and desorption performance may not be obtained, and if it exceeds 10 mmol / g, the moisture-absorbing resin particles absorb water and become greatly swollen into a gel state, resulting in insufficient water resistance. The amount of carboxyl groups here represents the molar amount of carboxyl groups relative to the particle weight when all the carboxyl groups of the resin particles are in the acid form.

[0013] In addition, the hygroscopic resin particles used in the present invention preferably have a crosslinked structure. Such a crosslinked structure reduces swelling of the particles that occurs when the particles absorb moisture or water. There are no particular limitations on the crosslinked structure, so long as it is not physically or chemically modified by moisture absorption or release, and any structure such as crosslinking by covalent bonds, ionic crosslinking, crosslinking by polymer molecular interactions or crystalline structures may be used. Among these, a crosslinked structure by covalent bonds is most preferable from the viewpoint of strength and stability.

[0014] Furthermore, it is preferable that the hygroscopic resin particles have good film-forming properties, and for this purpose, it is preferable that the hygroscopic resin particles have many crosslinked structures near the center and have almost no crosslinked structures at the surface layer. In such a structure, the polymer chains at the surface layer of the particles spread widely due to the electrical repulsion of the carboxylate ions when the carboxyl groups are dissociated in water, etc., and the particle diameter also increases. In other words, it is possible to spread the polymer chains three-dimensionally, which strengthens the entanglement of the polymer chains between the hygroscopic resin particles, and therefore it is thought that good film-forming properties are easily exhibited.

[0015] An example of the hygroscopic resin particles having such good film-forming properties is the hygroscopic polymer particles disclosed in WO 2015 / 111610, that is, the hygroscopic polymer particles are polymer particles having a crosslinked structure with carboxyl groups, a carboxyl group amount of 3 to 10 mmol / g when all of the carboxyl groups are converted to an acid form, and having film-forming properties, and characterized in that when the particles are dispersed in water to a content of 10% by weight, the viscosity is 500 mPa s or less.

[0016] Furthermore, the particle diameter of the hygroscopic polymer particles when dispersed in water is preferably at least four times the particle diameter when all the carboxyl groups in the particles are converted to acid form and then dispersed in water. Also, the hygroscopic polymer particles can be obtained by polymerizing a first monomer group containing a crosslinking monomer, then adding a second monomer group containing a monomer having a functional group that can be converted to a carboxyl group by hydrolysis, and polymerizing the resulting particles, and then hydrolyzing the particles.

[0017] In the present invention, the binder component is a general term for a crosslinking agent having a plurality of epoxy groups, which will be described later, a polymer resin for improving the adhesion between hygroscopic resin particles, and the like, and one or more kinds may be used. Here, as the polymer resin, one that can follow the volume change caused by the shrinkage of the hygroscopic resin particles when they are dried and the swelling when they are wet is preferable, and from this viewpoint, one having a glass transition point of 50° C. or less is preferable. Examples of such polymer resins include urethane resins, acrylic resins, and epoxy resins, and among them, water-based urethane resins that are excellent in adhesion and moisture permeability and have good dispersibility in the coating liquid described later are preferable.

[0018] The ratio of the binder component is preferably 1 to 10 parts by weight for the crosslinking agent and 10 to 50 parts by weight for the polymer resin, relative to 100 parts by weight of the moisture-absorbing resin particles. If the ratio of the crosslinking agent is too high, when the coating liquid described below is prepared, it solidifies in a short time, shortening the life of the coating liquid and causing deterioration of the handleability, which is undesirable. If the ratio is too low, sufficient crosslinking cannot be imparted to the moisture-absorbing resin particles, resulting in deterioration of the water resistance. If the ratio of the polymer resin is too high, the ratio of the polymer resin covering the moisture-absorbing resin particles will be high, which may cause a decrease in the moisture permeability of the moisture absorbing and releasing sheet, and if the ratio is too low, there is a concern that the water resistance will deteriorate, which is undesirable.

[0019] The sheet-shaped molded product in the present invention is a thin film-shaped molded product containing the above-mentioned moisture-absorbing resin particles and binder component. This sheet-shaped molded product may be composed of a substrate, moisture-absorbing resin particles, binder component, etc., as described below, or may not contain a substrate. In addition, as long as the effects of the present invention can be exhibited, the molded product may contain components other than the moisture-absorbing resin particles, binder component, and substrate.

[0020] The cationic polymer used in the present invention is a polymer that has at least one primary or secondary amino group in the molecule and can be positively charged by ionizing the polymer chain in an aqueous solution. The more cationic groups contained in this cationic polymer per unit weight, the more crosslinking points can be formed with the hygroscopic resin particles, which is industrially preferable, and the larger the molecular weight, the more preferable it is because water resistance is improved.

[0021] The cationic polymer used in the present invention is preferably a polyfunctional polyamine having a primary or secondary amino group. In the present invention, the polymer plays a role in improving water resistance by forming an ionic bond with the hygroscopic resin particles and further by forming a covalent bond with the crosslinking agent, but if the cationic group is a tertiary amino group or a quaternary ammonium group, it is not preferable because it is extremely difficult to form a covalent bond with the crosslinking agent. Also, if the cationic group is a monofunctional polyamine, the ionic bond with the hygroscopic resin particles is formed only at one place on the polymer, and water resistance cannot be improved, which is not preferable.

[0022] Examples of such cationic polymers include polyallylamine, polyethyleneimine, polydimethyldiallylammonium chloride, etc. Among them, polyethyleneimine is preferred because it has a large amount of amino groups per unit weight, can suitably form a network polymer with the hygroscopic resin particles (described later), and is commercially available as a relatively high molecular weight product.

[0023] The crosslinking agent that can be used as the binder component or the crosslinking agent that can be used in combination with the cationic polymer is not particularly limited, but is preferably one having two or more epoxy groups. This is because it is highly reactive with both the carboxyl group of the hygroscopic resin particles and the cationic group of the cationic polymer. Specific examples of the compound include glycerol diglycidyl ether, ethylene glycol diglycidyl ether, and propylene glycol diglycidyl ether.

[0024] In addition, the network polymer in the present invention refers to a polymer in which the above-mentioned cationic polymer is bonded by a crosslinking agent, and forms a very strong crosslink, which contributes to improving water resistance.In addition, it is preferable that the network polymer and the moisture-absorbing resin particles form a covalent bond by a crosslinking agent, and also form an ionic bond with each other from the viewpoint of improving water resistance.In addition, by adjusting the ratio of the moisture-absorbing resin particles, the cationic polymer, and the crosslinking agent used, it is possible to maintain the moisture permeability that is essential for the water-resistant moisture-absorbing and desorbing sheet of the present invention.

[0025] In order for the water-resistant moisture-absorbent sheet of the present invention to achieve the performance described below, the content of the moisture-absorbent resin particles, cationic polymer, and crosslinking agent (excluding the crosslinking agent as the binder component) in the moisture-absorbent sheet is 40 to 70 g / m. 2 , 4~40g / m 2 , and 0.3 to 3 g / m 2 It is preferable that the content of the hygroscopic resin particles is 40 g / m 2 If it is less than 70 g / m, sufficient moisture absorption cannot be maintained, which is not preferable. 2 If the content of the cationic polymer is more than 4 g / m, the amount of the resin particles relative to the substrate sheet is too large, and water resistance may be reduced. 2 If the cationic polymer is less than 40 g / m, the network polymer cannot be formed and the water resistance is reduced, which is not preferable. 2 If the content of the crosslinking agent is more than 0.3 g / m, a considerable amount of cationic polymer cannot form a network polymer, which also causes a decrease in water resistance, and is therefore undesirable. 2 If the density is less than 3 g / m, the network polymer described above cannot be sufficiently formed, which is not preferable. 2 If the amount is larger than this, the life of the coating liquid when producing the moisture absorbing and desorbing sheet is shortened, similarly to the case where it is used as the binder component described above, and therefore this is not preferred.

[0026] The substrate used in the present invention is not particularly limited, but may be a paper made from commonly used cellulose, a paper made from glass fiber or the like used in special paper applications, or a film made from a synthetic resin such as PET or urethane. From the viewpoint of moisture permeability, the substrate preferably has continuous holes, and the size and number of the continuous holes are preferably such that many hygroscopic resin particles can penetrate into the substrate.

[0027] The water-resistant moisture-absorbent and desorbent sheet of the present invention may contain components other than the above-mentioned components, so long as the effects of the present invention can be exhibited.

[0028] In addition, the water-resistant moisture-absorbent sheet of the present invention has an air permeability of 5 ml / (m 2 ·Pa·s) or less, and the moisture permeability measured by the method described below is 3000g / m 2 ·day or more is preferable, and 4000g / m 2 ·day or more is preferable. Air permeability is 5ml / (m 2 If the moisture permeability is higher than 3000g / m2, it indicates that the moisture absorption and release sheet is damaged by immersion in water and a certain amount of gas is passing through the moisture absorption and release sheet, which is undesirable because it causes a large loss of thermal energy. 2 If the durability is less than one day, it may be possible to use it as a component material for a large ventilation and air conditioning system, but for small systems such as those for vehicles, the area of ​​the moisture absorption and desorption sheet that can be used will be limited due to the system size restrictions, and there is a risk that the required performance will not be achieved, which is not preferable.

[0029] Next, an example of a method for producing the water-resistant moisture absorbing and releasing sheet of the present invention described above will be shown. This example is an example in which a substrate is used, and a coating liquid containing moisture absorbing resin particles and a binder component is applied to the substrate described above to produce a sheet-shaped molded product, and then a coating liquid containing a cationic polymer and a crosslinking agent is applied to the substrate. The method for producing the sheet-shaped molded product will be described in detail below.

[0030] First, a coating liquid containing hygroscopic resin particles (coating liquid 1) is prepared. In addition to the hygroscopic resin particles, an epoxy-based crosslinking agent, a urethane-based binder, or the like can be used as a binder component in coating liquid 1. Furthermore, at this time, an acidic compound may be added to further improve the reactivity of the epoxy-based crosslinking agent. The acidic compound added at this time may be an inorganic acid such as hydrochloric acid, sulfuric acid, or nitric acid, or may be a polyacrylic acid-based acidic polymer.

[0031] The coating solution 1 prepared by mixing these chemicals is applied to the above-mentioned substrate and dried to obtain a sheet-shaped molded product. Coating methods such as coating, immersion, and spraying can be used. There are no particular limitations on the drying conditions, but drying at 100°C or higher is preferable in order to efficiently evaporate water and to effectively promote the crosslinking reaction.

[0032] Next, a coating liquid (coating liquid 2) containing a cationic polymer and a crosslinking agent is prepared. In this case, the degree of neutralization of the cationic groups contained in the cationic polymer is important; as the degree of neutralization increases, the reaction with the crosslinking agent becomes less likely to occur, but it becomes easier to form ionic bonds with the moisture-absorbing resin particles, which is advantageous for producing a moisture-absorbing and desorbing sheet with higher water resistance. The degree of neutralization here indicates the extent to which the cationic groups have been neutralized; for example, when neutralizing primary amino groups with hydrochloric acid, if all primary amino groups are in the NH2 type, the degree of neutralization is 0%, and if all primary amino groups are in the NH3 type, the degree of neutralization is 0%. + Cl - If the cationic group is in this form, the degree of neutralization is expressed as 100%. In order to achieve a situation advantageous for improving water resistance as described above, the degree of neutralization of the cationic group is preferably 0% to 50%.

[0033] The degree of neutralization can be adjusted by adding an acidic compound to the coating liquid. The acidic compound is not particularly limited, but may be a general inorganic acid such as hydrochloric acid, nitric acid, or sulfuric acid, or may be an organic acid such as acetic acid, propionic acid, malonic acid, malic acid, oxalic acid, or succinic acid.

[0034] The crosslinking agent added to the coating liquid 2 is preferably about 5 to 30% by weight based on the weight of the cationic polymer, and preferably has two or more epoxy groups as described above.

[0035] In addition, the coating liquid 2 is preferably an aqueous solution or an aqueous solution containing a small amount of a hydrophilic organic solvent. In the process in which the coating liquid 2 permeates the above-mentioned sheet-shaped molded product, ionic crosslinks are introduced between the cationic polymer and the hygroscopic resin particles contained in the coating liquid 2, improving the strength of the coating film. In this process, if the coating liquid 2 contains a large amount of a hydrophilic organic solvent, the coating liquid 2 does not permeate the coating film sufficiently, and ionic crosslinks are only introduced on the surface of the coating film, so that sufficient water resistance of the coating film may not be obtained. On the other hand, it is expected that the inclusion of a hydrophilic organic solvent in the coating liquid 2 reduces the swelling of the hygroscopic resin particles, thereby preventing them from falling off. In light of these points, when a hydrophilic organic solvent is used in the coating liquid 2, the amount is preferably in the range of 0.1 to 50% by weight of the weight of the coating liquid 2.

[0036] The above-mentioned coating liquid 2 is applied to a sheet-shaped molded product and dried to obtain the water-resistant moisture-absorbing and desorbing sheet of the present invention. The adjustment of the coating amount of the coating liquid is not particularly limited, but the viscosity of the coating liquid 2 can be adjusted in advance using a thickener such as PVA, or the coating liquid can be squeezed using a machine such as a roller to adjust the coating amount. In addition, the drying temperature at this time is preferably 100°C or higher for the same reasons as in the drying of the above-mentioned coating liquid 1.

[0037] As described above, the reason why coating liquid 1 and coating liquid 2 are applied separately is that the hygroscopic resin particles and cationic polymer contained in each coating liquid immediately form an ionic crosslinked structure and aggregate when they come into contact in the coating liquid. In addition, although it is possible to make the hygroscopic resin particles and the cationic polymer exist in the same coating liquid without aggregating by adjusting the pH, in this case, the network polymer is not sufficiently formed and the water resistance is significantly reduced, which is not preferable. In addition, coating liquid 1 and coating liquid 2 may contain components other than the above-mentioned components as long as the effects of the present invention can be obtained.

[0038] The water-resistant moisture-absorbing and desorbing sheet of the present invention described above has both high moisture permeability and low air permeability, and can maintain these properties even after getting wet. Therefore, the water-resistant moisture-absorbing and desorbing sheet of the present invention can be suitably used as a constituent material of an element for moisture absorption and desorption or latent heat exchange. Such an element for moisture absorption and desorption or latent heat exchange is not particularly limited, but is preferably produced by laminating the above-mentioned water-resistant moisture-absorbing and desorbing sheets. By adopting a laminated form, it is possible to increase the contact area with the air that is the subject of moisture absorption and desorption or latent heat exchange, and it is also possible to mold it so that the pressure loss can be kept low, which is practically advantageous. As such a laminated form, for example, as shown in FIG. 1, a corrugated sheet and a corrugated paper made of the water-resistant moisture-absorbing and desorbing sheet of the present invention on a flat plate may be laminated alternately so as to be perpendicular to each other to provide an air flow path, or a structure in which a rod-shaped member such as plastic is arranged at intervals instead of the corrugated sheet in FIG. 1 to provide an air flow path may be used.

[0039] Examples of applications of the water-resistant moisture absorbing and releasing sheet or latent heat exchange element of the present invention include, but are not limited to, applications in ventilation air conditioning systems. EXAMPLES

[0040] Examples are shown below to facilitate understanding of the present invention, but these are merely illustrative and the gist of the present invention is not limited to these.

[0041] <Method for evaluating the amount of carboxyl groups> 1 g of thoroughly dried sample was precisely weighed (X [g]), 200 ml of water was added, and then 1N hydrochloric acid was added while heating to 50°C to adjust the pH to 2, converting all the carboxyl groups in the sample to acid carboxyl groups, and a titration curve was then obtained using a 0.1N NaOH aqueous solution according to the usual method. The amount of NaOH aqueous solution consumed by the acid carboxyl groups (Y [ml]) was obtained from the titration curve, and the amount of carboxyl groups in the sample was calculated using the following formula. Carboxyl group amount [mmol / g] = 0.1Y / X

[0042] <Air permeability evaluation method> The gas permeability test mode of the "Envelope Surface Area Analyzer" manufactured by Porous Materials, Inc. was used to pass nitrogen gas through the sample sheet and measure the flow rate of the gas passing through the sample sheet. This measurement was carried out multiple times by changing the pressure according to the above test mode, and the air permeability [ml / (m 2 The lower this value, the lower the breathability of the sheet can be determined.

[0043] <Method for evaluating air permeability after immersion in water> A sample sheet measuring 5 cm x 7.5 cm was prepared and placed in a plastic tray measuring 9.5 cm in length, 6.5 cm in width, and 1.3 cm in depth, and distilled water at 20°C was slowly added so that the sample sheet was fully immersed. After 5 minutes, the sample sheet was carefully removed and dried in a 120°C dryer for 30 minutes. The air permeability after immersion in water was then measured using the same method as the air permeability evaluation method described above.

[0044] <Method for evaluating moisture permeability> The sample sheets were measured under conditions of 40° C. and 90% RH using a moisture permeability measuring device (Lessy L80-5000, manufactured by Systec Illinois).

[0045] <Calculation method of neutralization degree of cationic polymer in coating solution 2> The degree of neutralization is calculated according to the following formula using A, the number of moles of the cationic group contained in the cationic polymer used to prepare Coating Solution 2, B, the number of moles of the cationic group, C, and the number of moles of the anion generated from the acidic compound, D, and the valence of the anion. Neutralization degree [%] = {(C × D) / (A × B)} × 100

[0046] <Contents of hygroscopic resin particles having carboxyl groups, cationic polymer and crosslinking agent> 1. Content of hygroscopic resin particles The weight ratio of the hygroscopic resin particles in the solid content of Coating Liquid 1 is a [%], and the weight increase per unit area before and after the substrate sheet is impregnated with Coating Liquid 1 and dried is W1 [g / m 2 ] was calculated using the following formula. Moisture-absorbing resin particle content [g / m 2 ]=W1×a / 100 2. Content of cationic polymer and crosslinking agent The weight percentage of the cationic polymer in the solid content of Coating Liquid 2 is b [%], the weight percentage of the crosslinking agent is c [%], and the weight increase per unit area before and after impregnation and drying with Coating Liquid 2 is W2 [g / m 2 ] was calculated using the following formula. Cationic polymer content [g / m 2 ]=W2×b / 100 Crosslinking agent content [g / m 2 ]=W2×c / 100

[0047] [Example 1] As the hygroscopic resin particles, 100 parts by weight, calculated as solid content, of the hygroscopic polymer particle aqueous dispersion disclosed in Example 1 of WO 2015 / 111610 was used, to which 1 part by weight, calculated as solid content, of a polyacrylic acid aqueous solution as an acidic compound, 30 parts by weight, calculated as solid content, of Superflex 500M (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), an aqueous dispersion of urethane resin as a binder component, and 5 parts by weight of ethylene glycol diglycidyl ether (hereinafter also referred to as EGDGE), also as a binder component, were mixed to prepare coating liquid 1. This was applied to a coating solution having a basis weight of 25 [g / m 2 ], air permeability 5800[ml / (m 2 A porous sheet mainly composed of glass fibers with a molecular weight of 1.0 Pa s was impregnated with the coating solution and then dried, resulting in a coating liquid with a loading of 65 g / m 2 A sheet-like molded product having the above composition was obtained. Next, 200 parts by weight of polyethyleneimine P-1000 (manufactured by Nippon Shokubai, weight average molecular weight 70,000) as a cationic polymer, 373 parts by weight of 1N HCl as an acidic compound for adjusting the degree of neutralization, and 1 part by weight of EGDGE as a crosslinking agent were mixed to prepare coating liquid 2. This was impregnated and coated on the above sheet-like molded product, and then dried to produce a water-resistant moisture-absorbing and desorbing sheet. The various evaluation results are shown in Table 1.

[0048] The above-mentioned water dispersion of hygroscopic polymer particles can be prepared as follows. That is, 440 parts by weight of water, 4 parts by weight of Eleminol MON-7 (manufactured by Sanyo Chemical Industries), 3 parts by weight of methyl methacrylate, and 15 parts by weight of divinylbenzene are added to a reaction tank, and the temperature is raised to 60°C. Next, 196 parts by weight of methyl acrylate, 2 parts by weight of methacrylic acid, 70 parts by weight of a 1.3% by weight aqueous sodium pyrosulfite solution, and 70 parts by weight of a 1.5% by weight aqueous ammonium persulfate solution are added to the reaction tank over a period of 2 hours, and polymerization is performed to obtain a precursor emulsion of hygroscopic polymer particles. 38 parts by weight of potassium hydroxide and 782 parts by weight of water are added to 100 parts by weight of the solid content of the obtained precursor emulsion, and the mixture is heated at 90°C for 16 hours to carry out a hydrolysis reaction to obtain a water dispersion of hygroscopic polymer particles. The average particle size of the hygroscopic polymer particles is 930 nm, and 120 nm when all carboxyl groups are converted to acid type, with a particle swelling ratio of 7.8.The viscosity of a 10% aqueous dispersion is 200 mPa s, and the film-forming properties are also good.

[0049] [Examples 2 and 3] Water-resistant moisture absorbing and releasing sheets were produced in the same manner as in Example 1, except that the amount of EGDGE in Coating Liquid 2 was 0.5 parts by weight in Example 2 and 2 parts by weight in Example 3. The results of various evaluations are shown in Table 1. Note that in Example 3, the pot life of Coating Liquid 2 tended to be shorter.

[0050] [Examples 4 and 5] Water-resistant moisture absorbing and releasing sheets were prepared in the same manner as in Example 1, except that the amount of polyethyleneimine P-1000 in Coating Solution 2 was changed to 280 parts by weight in Example 4 and 160 parts by weight in Example 5. The results of various evaluations are shown in Table 1.

[0051] [Examples 6 and 7] Water-resistant moisture absorbing and releasing sheets were prepared in the same manner as in Example 1, except that the 373 parts by weight of 1N HCl in the coating liquid was changed to 373 parts by weight of water in Example 6, and to 373 parts by weight of 2N HCl in Example 7. The results of various evaluations are shown in Table 1.

[0052] [Examples 8 and 9] In Example 1, 200 parts by weight of polyethyleneimine P-1000 and 373 parts by weight of 1N HCl in coating liquid 2 were replaced with 400 parts by weight of polyallylamine PAA-01 (manufactured by Nittobo Medical, solid content 15%, weight average molecular weight 1600) and 173 parts by weight of 2.16N HCl in Example 8, and with 400 parts by weight of polyallylamine PAA-15C (manufactured by Nittobo Medical, solid content 15%, weight average molecular weight 15000) and 173 parts by weight of 2.16N HCl in Example 9. A water-resistant moisture absorbing and releasing sheet was produced in the same manner. Various evaluation results are shown in Table 1.

[0053] [Comparative Example 1] The sheet-like molded product obtained in Example 1 on which Coating Liquid 2 was applied and not dried was subjected to various evaluations. The results are shown in Table 1.

[0054] [Comparative Example 2] A moisture absorbing and desorbing sheet was produced in the same manner as in Example 1, except that EGDGE was not added to Coating Liquid 2. The results of various evaluations are shown in Table 1.

[0055] [Comparative Example 3] A moisture absorbing and desorbing sheet was produced in the same manner as in Example 1, except that polyethyleneimine P-1000 was not added to Coating Liquid 2. The results of various evaluations are shown in Table 1.

[0056] [Table 1]

[0057] As shown in Table 1, each sheet of Comparative Examples 1 to 3 using Coating Solution 2 that does not contain either or both of a cationic polymer and a crosslinking agent has high moisture permeability, but the air permeability after immersion in water increases sharply compared to the air permeability before immersion in water, indicating low water resistance. On the other hand, the sheet shown in Example 2 etc. has a moisture permeability of 3000 g / m 2·day or more, and the air permeability after immersion in water is also 5ml / (m 2 ·Pa·s), it can be said that this is a moisture absorption and release sheet with sufficiently high water resistance. [Explanation of symbols]

[0058] 1: Water-resistant moisture-absorbing and moisture-releasing sheet on a flat plate 2: Corrugated sheet 3: Air flow through one of the channels 4: Air flow through the other flow path

Claims

1. The water-resistant moisture absorbing and releasing sheet comprises a sheet-shaped molding containing moisture absorbing resin particles having carboxyl groups and a binder component, and a network polymer containing a cationic polymer and a crosslinking agent.

2. 2. The water-resistant moisture-absorbent and desorbent sheet according to claim 1, wherein the sheet-like molded product includes a substrate.

3. Moisture permeability is 3000g / m 2 day or more, and the air permeability after immersion in water at 20°C for 5 minutes and then drying at 120°C for 30 minutes is 5 ml / (m 2 3. The water-resistant moisture-absorbent sheet according to claim 2, characterized in that the water-resistant moisture-absorbent sheet has a viscosity of not more than 1.5 Pa·s.

4. 4. The water-resistant moisture absorptive and desorptive sheet according to claim 1, wherein the moisture-absorbent resin particles having carboxyl groups have 3 to 10 mmol / g of carboxyl groups.

5. The content of the hygroscopic resin particles having a carboxyl group, the content of the cationic polymer and the content of the crosslinking agent are each 40 to 70 g / m 2 , 4 to 40 g / m 2 and 0.3 to 3 g / m 2 5. The water-resistant moisture-absorbent and -desorbent sheet according to claim 1,

6. 6. The water-resistant moisture-absorbing and desorbing sheet according to claim 1, wherein the cationic polymer is a multifunctional polyamine having a primary or secondary amine.

7. 7. The water-resistant moisture-absorbing and desorbing sheet according to claim 1, wherein the crosslinking agent has two or more epoxy groups.

8. A method for producing a water-resistant moisture-absorbent sheet, comprising the steps of impregnating a sheet-shaped molded product containing moisture-absorbent resin particles having carboxyl groups and a binder component with a coating liquid containing a cationic polymer and a crosslinking agent, and then drying and reacting the material.

9. A moisture absorbing / desorbing or latent heat exchanging element comprising the water-resistant moisture absorbing / desorbing sheet according to any one of claims 1 to 7 as a constituent material.

10. A ventilation and air conditioning system using the element according to claim 9.

Citation Information

Patent Citations

  • Sorbent coating liquid, sorbent-supported metallic plate coated with sorbent coating liquid, and heat exchanger possessing sorbent-supported metallic plate

    JP2014180637A

  • Hygroscopic fiber structure

    JP2019118899A

  • Hygroscopic polymer particles, as well as sheet, element, and total heat exchanger having said particles

    WO2015111610A1

  • Total heat exchange element and total heat exchanger

    WO2019180834A1